A high torque density dual-permanent-magnet machine for electric vehicle applications - Chathayil, Vaishnav (Nanyang Technological University, 2024)
The main objective of this work is to design a modern electric motor that is suitable for EV applications. In a conventional EV powertrain, it would house a high-speed motor with a mechanical gear system to achieve its desired torque performance. However, this would indulge in multiple disadvantages such as friction and windage losses, along with an increase in effective weight of the entire powertrain system (due to the gear assembly). To eliminate these issues, a direct-drive motor can serve as an alternative, avoiding the use of gears and transmitting the torque directly to the vehicle’s wheel.